(untitled) (Jurnal Bahasa, 2015)
This paper discusses the morphological process of truncation in Malay names. This study uses primary data collected from observations made at the School of Language Studies and Linguistics as well as through the social networking site, Facebook. The names were gathered from students of this school. The research focuses on the process of truncation of full names. The analysis was conducted to investigate the truncation of names based on the approach in prosodic morphology theory called morpheme-based template, which has been developed within the optimality theory. The results of this analysis could explain how the process of disyllabic and monosyllabic truncations occur in Malay. Keywords: Malay, names truncation, prosodic morphology, morpheme-based-template, optimality